Spinal infection: state of the art and management algorithm - Duarte, Rui M. (2013)
Spinal infection is a rare pathology although a concerning rising incidence has been observed in recent years. This increase might reflect a progressively more susceptible population but also the availability of increased diagnostic accuracy. Yet, even with improved diagnosis tools and procedures, the delay in diagnosis remains an important issue. This review aims to highlight the importance of a methodological attitude towards accurate and prompt diagnosis using an algorithm to aid on spinal infection management. METHODS: Appropriate literature on spinal infection was selected using databases from the US National Library of Medicine and the National Institutes of Health. RESULTS: Literature reveals that histopathological analysis of infected tissues is a paramount for diagnosis and must be performed routinely. Antibiotic therapy is transversal to both conservative and surgical approaches and must be initiated after etiological diagnosis. Indications for surgical treatment include neurological deficits or sepsis, spine instability and/or deformity, presence of epidural abscess and upon failure of conservative treatment. CONCLUSIONS: A methodological assessment could lead to diagnosis effectiveness of spinal infection. Towards this, we present a management algorithm based on literature findings.